Retrospectiva das investigações e metodologias no estudo do Paleolítico Inferior no Vale do Tejo em território português - Cura, Sara (Trabalhos de Antropologia e Etnologia, 2020)
The present work displays a retrospective of the research and methodologies applied in the study of the Lower Paleolithic of the Tagus valley in Portuguese territory. Within the scope of the Portuguese Lower Paleolithic this is the most studied region, being pioneer in the research already in the end of the XIX century. With more than one century of research there are several sites which are national reference for the Lower Paleolithic studies. Their history of research reflects, in the methodologies, the international evolution of the archeology of this epoch. Nevertheless in Portugal the methodological advances arrived always with retard if compared with their references, mainly the French school and more recently the anglo-saxonic and northern American schools. Despite being the most studied region for Lower Paleolithic research, is far from exhaust its informative potential especially in the light of the most recent methodological frameworks here applied.